Genetic causality of lipidomic and immune cell profiles in ischemic stroke - Chen, Haohao; Zheng, Zequn; Cai, Xiaorui; Li, Shunxian; Chen, Manli; Wu, Jiaming; He, Wenzhen; Gao, Fenfei (Frontiers in Neurology, 2024)
Background Ischemic stroke (IS) is a global health issue linked to lipid metabolism and immune cell responses. This study uses Mendelian randomization (MR) to identify genetic risk factors for IS subtypes using comprehensive genetic data from lipidomic and immune cell profiles. Methods We assessed genetic susceptibility to IS across 179 lipids and 731 immune cell phenotypes using instrumental variables (IVs) from recent genome-wide association studies. A two-sample MR approach evaluated correlations, and a two-step MR mediation analysis explored the role of immune cell phenotypes in the lipid-IS pathway. Sensitivity analyses, including MR-Egger and Cochran Q tests, ensured robust results. Results Genetic IVs for 162 lipids and 614 immune cell phenotypes were identified. Significant genetic causality was found between 35 lipids and large artery stroke (LAS), with 12 as risk factors (sterol esters, phosphatidylcholines, phosphatidylethanolamines) and 23 as protective factors (phosphatidylcholines, phosphatidylethanolamines, phosphatidylinositols). For small vessel stroke (SVS), 8 as risk factors (sterol esters, phosphatidylcholines), and 2 as protective factors (phosphatidylinositol, sphingomyelin). For cardioembolic stroke (CS), 2 as risk factors, and 4 as protective factors. Mediation analysis revealed that CCR2 on granulocytes, CD11c on CD62L+ myeloid dendritic cells, and FSC-A on granulocytes mediated the lipid-immune cell-LAS pathway, while CD4 on activated CD4 regulatory T cells and CD4 on activated & secreting CD4 regulatory T cells mediated the lipid-immune cell-SVS pathway. Conclusion This study identifies genetic links between specific lipids and IS subtypes, highlights immune cells’ role in IS risk and mediation, suggests new therapeutic targets, and uncovers IS genetic drivers.